AUTOMOBILE TRANSMISSION SHAFT ASSEMBLY STATIC AND DYNAMIC CHARACTERISTICS ANALYSIS - PAN Yu (Jixie qiangdu)
The transmission shaft is a critical component of the automobile transmission system,it’s static and dynamic characteristics good or bad is directly related to the safety and NVH problems of vehicle.To solve these problems,using Abaqus software establish the finite element model of the transmission shaft assembly strength and modal analysis,and through the modal experiment verifies the correctness of the finite element simulation analysis model,point out that the reliability of the analytical method,and through the theoretical calculation verify it,results show that the strength and modal of the transmission shaft assembly are meet the requirements of the vehicle matching design,the method provides a theoretical basis for the transmission shaft static and dynamic design.